Evaluation of Antibiotic Prescribing Patterns in Hospitalised Cellulitis Patients: A Prospective Drug Utilisation Study (World Journal of Current Medical and Pharmaceutical Research, 2026)
Cellulitis is a common bacterial infection involving the skin and subcutaneous tissues that requires timely and appropriate antibiotic therapy to prevent complications. However, empirical and inappropriate antibiotic prescribing contributes to antimicrobial resistance and adversely affects treatment outcomes. The present prospective observational study evaluated antibiotic prescribing patterns and their adherence to standard treatment guidelines among hospitalized cellulitis patients using drug utilization metrics. The study was conducted over six months in the Department of Surgery of a tertiary care hospital and included 100 inpatients diagnosed with cellulitis. Data were collected from patient case records, medication charts, and laboratory reports. Antibiotic utilization was assessed using the World Health Organization (WHO) Defined Daily Dose (DDD) and Drug Utilization 90% (DU90%) methodologies, while descriptive statistics, Chi-square test, and ANOVA were used for data analysis. Most patients belonged to the 41–60-year age group (68%), with males accounting for 65% of cases. Lower limb cellulitis was the predominant clinical presentation (74%). Ceftriaxone (46%) was the most frequently prescribed antibiotic, followed by amoxicillin–clavulanate (17%) and clindamycin (16%). DU90% analysis identified ceftriaxone, amoxicillin–clavulanate, linezolid, and clindamycin as the most commonly utilized antibiotics. The overall recovery rate was 73%, although severe cases were associated with longer hospital stays and lower recovery rates. A significant association was observed between disease severity and duration of hospitalization (p < 0.05). The findings emphasize the need to strengthen guideline-based prescribing, encourage culture-directed antibiotic therapy, and implement antimicrobial stewardship programs to optimize antibiotic use and minimize antimicrobial resistance.